Preliminary study on association of β2 - adrenergic receptor polymorphism with hypertension in hypertensive subjects attending Balok Health Centre, Kuantan - Ahmed Elbadri, Atia; Ku Zaifah, Norsidah; Abdullah, Nor Zamzila; Mokhtar, Rafidah Hanim; Draman, Samsul; Md Aris, Mohd Aznan; Abdul Rahman, Rashidah; A.Talib, Norlelawati (Malaysian Medical Association, 2012)
Polymorphisms within the beta2-adrenergic receptor (ADRB2) gene have been repeatedly linked to hypertension. Among the ADRB2 polymorphisms detected, Arg16Gly and Gln27Glu codons are considered the two most important variations. The amino acid substitution at these codons may lead to abnormal regulation of ADRB2 activity. The aim of the present study was to assess the association between ADRB2 polymorphisms and hypertension. This case-control study consisted of 100 unrelated subjects (50 hypertensive and 50 matched normal controls). Arg16Gly and the Gln27Glu polymorphisms were analyzed by polymerase chain reaction-restriction fragment length polymorphism assay. There were no significant evidence of association in allelic and genotypes distribution of Arg16Gly and Glu27Gln with blood pressure and hypertension. These findings suggest that the variation within codon 16 and 27 of ADRB2 gene were unlikely to confer genetic susceptibility for hypertension in our population samples.